2016
DOI: 10.1080/02755947.2016.1165774
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Juvenile Cutthroat Trout Translocated as Embryos from Five Populations into a Common Habitat

Abstract: The distributions of most native trout species in western North America have been severely reduced, and conservation of many of these species will require translocation into vacant habitats following removal of nonnative species. A critical question managers have is “Does it matter which donor sources are used for these translocations?” We present a case study that addressed this question for a large native trout translocation project in Montana. We introduced embryos from five source populations of Westslope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…More complex river branching patterns may reduce gene flow and provide an opportunity for local differentiation [ 25 , 65 , 66 ]. This substantial differentiation may also involve local adaptation to spatial and temporal variation among the stream environments [ 67 , 68 , 69 ]. We know that resident salmonid morphology [ 12 ], growth [ 70 ], and movement [ 71 ], for example, differ in these traits from their respective anadromous life history form.…”
Section: Discussionmentioning
confidence: 99%
“…More complex river branching patterns may reduce gene flow and provide an opportunity for local differentiation [ 25 , 65 , 66 ]. This substantial differentiation may also involve local adaptation to spatial and temporal variation among the stream environments [ 67 , 68 , 69 ]. We know that resident salmonid morphology [ 12 ], growth [ 70 ], and movement [ 71 ], for example, differ in these traits from their respective anadromous life history form.…”
Section: Discussionmentioning
confidence: 99%
“…This provides support for the general importance of maintaining genetic diversity in small populations and adds to the growing understanding of the importance of genetic diversity in small salmonid populations. For example, a recent study of westslope cutthroat trout ( Oncorhynchus clarkii lewisi ) that translocated embryos from five sources were translocated into a vacant habitat found that the juveniles from the most genetically diverse source populations had higher survival (Andrews et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to habitat size, the importance of connectivity for metapopulation persistence has been demonstrated for multiple salmonid species (e.g., Koizumi, ; Letcher et al., ). In response to anthropogenic barriers that disrupt metapopulation connectivity and reduce habitat size, translocations are becoming more widely considered in aquatic ecosystems (Andrews et al., ; Olden et al., ; Pavlova et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in many situations age and growth analyses using hard parts is preferred (Fleener 1952; Cooper 1970), or potentially tagging and recapture of wild fishes (Myrvold and Kennedy 2015; Uthe et al 2016). Nonetheless, there is an important place within fisheries science for growth experiments, especially when evaluating translocation potential of sensitive populations in the absence of other information (Andrews et al 2016). Translocation studies using caged fish are especially crucial to studying how Cutthroat Trout are limited by resources (Knight et al 1999; Boss and Richardson 2002).…”
Section: Methodsmentioning
confidence: 99%